The Effect of I-131 Treatment on Complete Blood Count - Sahutoglu, G.; Cetin, S. K.; Atilgan, H. I. (National Research and Innovation Agency, 2024)
Radioactive iodine-131 (RAI) treatment may cause suppression in the bone marrow. In this study, hemoglobin levels, leukocyte, thrombocyte, and lymphocyte counts will be compared before total thyroidectomy and 6 months after RAI treatment. 97 patients (76 females, 21 males) with a diagnosis of well-differentiated thyroid cancer who had undergone total thyroidectomy and received 50-200 mCi RAI treatment were included in the study. Hemoglobin levels, leukocyte, thrombocyte, and lymphocyte counts of the patients in the last month before the treatment and in the sixth month after the treatment were compared retrospectively. When the whole patients were analyzed, hemoglobin levels, leukocyte, thrombocyte, and lymphocyte counts in pretreatment were statistically lower than after-treatment values. While hemoglobin levels of female patients were similar before and after treatment, lymphocyte, thrombocyte, and leukocyte counts were statistically lower before treatment. Hemoglobin levels, leukocyte,and thrombocyte counts were similar before and after treatment, while lymphocytes decreased significantly after RAI treatment. Thyroid cancer patients who received 50-200 mCi RAI treatment after total thyroidectomy, have bone marrow suppression but are still in normal mean value ranges. This mild bone marrow suppression is more prominent in female patients than in male patients.